Physical and chemical characterization of Eucalyptus stumps and roots for bioenergy - Costa, Ana Carolina Lopes Amaral [UNESP]; Guerra, Saulo Philipe Sebastião [UNESP]; Spadim, Emanuel Rangel [UNESP]; De Souza Passos, José Raimundo [UNESP]; De Jesus Eufrade-Junior, Humberto [UNESP] (Instituto de Pesquisa e Estudos Florestais (IPEF), 2021)
The objective of this work was to determine the physical properties (moisture content wet basis - UBU and basic density - DB), the higher heating value (PCS) and the chemical composition of stumps and roots from different Eucalyptus clonal plantation and storage time. The stumps were chipped, stocked and sampled after 0, 15, 30, 45, 60, 75 and 90 days. For the statistical analysis of the properties and the variation factors, generalized linear models were adjusted and the treatments were compared by the Tukey-Kramer test (p <0.05). Among the studied clones, Eucalyptus grandis obtained the more interesting characteristics for bioenergy (PCS of 17.1 MJ kg-1, UBU of 26.2% and lower contents of ash and chlorine) and the storage did not affect the quality of the biomass. Stumps have the potential for power generation after harvesting from forest stands, although further studies should be conducted to evaluate the sustainable use of this residual biomass in Brazil.
Caracterização física e química de tocos e raízes de Eucalyptus para bioenergia
Keywords: Heating value; Proximate analysis; Storage; Woodchips